STUDI KOMPERATIF FUNGSI KERAPATAN OBSERVASI DENGAN FUNGSI KERAPATAN RAYLEIGH - Anasiru, Triyanti; Setiyawan, Setiyawan (MEKTEK, 2010)
Observation data time series, used input to determine characteristic wave sea. Parameter wave is important for the infrastructure sea. Inveterate method used analyse parameter wave analyse domain frequency in ensemble average.This writing is research aim to learn step process data field till got parameter wave for infrastructure planning sea.Method this writing is plot of original data time series, plot time series which zero-mean and eliminated trend, making tables & draw histogram frequency change face irrigate, making tables & draw function density change face irrigate, f(Î·), comparing function density which got, with function of Gauss density, calculated deviasi (Î´), or error, between function theoretical density with function density from data.To each data, conduct zero-upcrossing at data, to get high data wave. To each high data & perioda wave which got, making tables & draw histogram high frequency wave, making tables & draw function high density wave, calculating Hmax, H1/10, H1/3, Hrata2, Hmin and Tmax, T1/10, T1/3, Trata2, Tmin, HRMS, comparing function of density which got, with function of Rayleigh density, calculated deviasi (Î´), or error, between function theoretical density with function density from data